Tradisi Omed-Omedan Sebagai Bentuk Wisata Budaya Bagi Dunia Pariwisata Di Bali - I Wayan Titra Gunawijaya; Ni Putu Dian Utami Dewi (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2021)
Balinese culture is very diverse and there is no cultural similarity between one place and another, this gives a unique to every tradition it implements. Such as the implementation of the tradition omed-omedan / med-medan carried out by STT Banjar Kaja Desa Sesetan. Through qualitative approach and inform determination techniques using snowball method will certainly eliminate the data with the purpose of research. The data obtained is then defined qualitatively and presented in the form of narrative. This tradition has nothing in common with other traditions in Bali, of course this becomes the only mass kissing tradition in Bali. The existence of this unit tradition will certainly be interesting and have a selling point if then packaged neatly and interestingly in the form of cultural tourism presented. In the implementation of omed-omedan festival held a series of med-medan traditions, will certainly provide more value, especially those involved in the festival is the residents of Desa Sesetan as activists of cultural arts and entrepreneurship that can support the growth of the economic pace of the community. The festival is then packaged in the form of a performing arts festival and there are various stands both food and handicrafts as handmade.Keywords: Omed-omedan, cultural tourism